PENINGKATAN HASIL BELAJAR MATEMATIKA DALAM PEMAHAMAN KPK DAN FPB MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS 5 SD INPRES HARTACO INDAH - Auni Batrisyia A; Annisa Citra Suciwiana (STKIP Subang, 2024)
This study aims to determine whether there is an improvement in mathematics learning outcomes in identifying the Least Common Multiple (LCM) and Greatest Common Divisor (GCD) through the application of the STAD (Student Teams-Achievement Divisions) cooperative learning model among fifth-grade students at SD Inpres Hartaco Indah. The research follows the framework of classroom action research (CAR), where the identified problems are analyzed and addressed through a series of cyclical activities consisting of planning, implementation, observation, and reflection. If the issues are not resolved in one cycle, subsequent cycles may follow. This study involved two cycles, targeting 33 fifth-grade students from SD Inpres Hartaco Indah. The findings indicate an improvement in students' ability to determine powers and roots in mathematics through the STAD cooperative learning model. The results reveal that the average learning outcomes in Cycle II (82.26 or 82%) were higher than those in Cycle I (74.13 or 74%) and also surpassed students' previous achievements in mathematics. However, it is acknowledged that the implementation of the learning method was not fully optimized due to time constraints and individual differences among students. To further validate these findings, follow-up studies with similar research problems are recommended, conducted in different locations and with a broader scope.